1998
DOI: 10.1152/ajplung.1998.275.5.l1006
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and capsaicin release prostaglandin E2from rat intrapulmonary bronchi

Abstract: We hypothesized that substance P and capsaicin would cause the release of prostaglandin E2(PGE2) from intrapulmonary bronchi isolated from Sprague-Dawley rats. Substance P (1 μM) caused the release of PGE2, measured with enzyme immunoassay, from the isolated airway segments; PGE2 release was inhibited by the neurokinin (NK)1-receptor antagonist, RP-67580, by inhibition of cyclooxygenase with meclofenamate, and by removal of the epithelium. The release of PGE2 caused by capsaicin (1 μM) was similar in magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…The absence of significant correlation might be based on the fact that PGE 2 inhibits challenges that work indirectly via neural pathways or mediator release but not those that act predominantly via a direct action on airway smooth muscle, such as histamine and metacholine [2,3]. The above theory is partially supported by previous observations that PGE 2 inhibits acetylcholine release from cholinergic nerves [25], represents the ultimate mediator of airway smooth muscle relaxation produced by activation of sensory nerve inhibitory system [26], but fails to protect against bronchoconstriction induced by methacholine [27]. Another plausible explanation might be based on the theory that the inhibitory effect of PGE 2 in histamine-induced contraction appears to be concentration-dependent [28].…”
Section: Discussionmentioning
confidence: 88%
“…The absence of significant correlation might be based on the fact that PGE 2 inhibits challenges that work indirectly via neural pathways or mediator release but not those that act predominantly via a direct action on airway smooth muscle, such as histamine and metacholine [2,3]. The above theory is partially supported by previous observations that PGE 2 inhibits acetylcholine release from cholinergic nerves [25], represents the ultimate mediator of airway smooth muscle relaxation produced by activation of sensory nerve inhibitory system [26], but fails to protect against bronchoconstriction induced by methacholine [27]. Another plausible explanation might be based on the theory that the inhibitory effect of PGE 2 in histamine-induced contraction appears to be concentration-dependent [28].…”
Section: Discussionmentioning
confidence: 88%
“…Our present findings show that HK-1 and SP signal via both NK 1 and NK 2 receptors to induce PGE 2 release in colonic mucosa. It has been previously reported that SP/NK 1 receptors causes PGE 2 release from rat intrapulmonary bronchi (Szarek et al, 1998) and porcine jejunum (Thorbøll et al, 1998). Another study has demonstrated that SP stimulates PGE 2 release in human colonic epithelial cells stably transfected with NK 1 receptors (Koon et al, 2006), but such interactions have not been extensively studied in native human intestine.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 production is increased in IBD (Baumeister et al, 1996), and it has been suggested as a mediator and/or prognostic marker in IBD (Wierciń ska-Drapalo et al, 1999;Sheibanie et al, 2007). PGE 2 and tachykinins have two-way interactions, in that tachykinins can increase levels of PGE 2 in rat intrapulmonary bronchi (Szarek et al, 1998), whereas PGE 2 also stimulates SP release in rat sensory neurons (White, 1996). Although it is clear that abnormal levels of SP, HK-1, and PGE 2 all occur in IBD, and functional interaction between SP and PGE 2 has been reported in human colonic epithelial cells (Koon et al, 2006), a mechanistic link between HK-1 and PGE 2 production remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SP was also shown to induce COX-2 expression and NF-kB activation in human polymorphonuclear leukocytes (21). Additionally, SP stimulated PGE 2 via NK1R in isolated rat intrapulmonary bronchi and trachea preparations (22,23) and via PGE 2 R subtype 2 in murine tracheal preparations (24). However, the interactions between SP, COX-2, and PGE 2 in inducing remote ALI after severe local burn are not known.…”
mentioning
confidence: 99%